Molecular and clinical studies in 8 patients with Temple syndrome. Issue 6 (25th March 2018) - Gillessen‐Kaesbach, G.; Albrecht, B.; Eggermann, T.; Elbracht, M.; Mitter, D.; Morlot, S.; van Ravenswaaij‐Arts, C.M.A.; Schulz, S.; Strobl‐Wildemann, G.; Buiting, K.; Beygo, J.
Abstract : Temple syndrome (TS14, #616222) is a rare imprinting disorder characterised by phenotypic features including pre‐ and postnatal growth retardation, muscular hypotonia and feeding difficulties in infancy, early puberty and short stature with small hands and feet and often truncal obesity. It is caused by maternal uniparental disomies, paternal deletions and primary imprinting defects that affect the chromosomal region 14q32 and lead to a disturbed expression of imprinted genes in this region. Here, we present detailed clinical data of 8 patients with Temple syndrome, 4 with an imprinting defect, 2 with an imprinting defect in a mosaic state as well as 1 complete and 1 segmental maternal uniparental disomy of chromosome 14. Abstract : Temple syndrome is a rare imprinting disorder caused by genetic and epigenetic disturbances of the imprinted region on chromosome 14q32. Detailed clinical description of 8 patients with Temple syndrome due to different molecular causes (imprinting defects, mosaic imprint defects, maternal uniparental disomy of chromosome 14) and first description of a segmental maternal uniparental disomy of chromosome14q32 causing Temple syndrome.